A poética metaficcional de Sérgio Sant’ Anna N'o Voo da madrugada - Uavniczak, Odirlei Vianei (2014)
This study aims to investigate the existence of a metafictional poetics developed along the literary production of Sérgio Sant'Anna, which would culminate in the book O voo da madrugada (2003). The main goal is to show how it is possible to think O voo da madrugada as the resumption and systematization of Sérgio Sant Anna s work in which the writer would seek to transform in fictional matter the three instances of the literary process creation, work, reception which are themed, respectively, in the three parts into which the book is divided. For this purpose, first of all we sought to study the phenomenon of textual metafictionality in its relationship with postmodernism in order to check what is the specificity of contemporary metafiction and what modes and forms it may assume; later, the literary production of Sérgio Sant'Anna was analyzed in parallel to contemporary Brazilian literature, in order to investigate what are the metafictional trends assumed by Sant Anna s fiction and what is its position in the Brazilian literary scene, and then study how these trends converge systematically in the book O voo da madrugada.